2016
DOI: 10.1111/1756-185x.12919
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors of hand involvement in Thai patients with systemic sclerosis

Abstract: Our results confirm that dcSSc patients had more severe clinical hand complications than lcSSc. However, radiographic findings were similar among subgroups, except that more finger contractures were seen in dcSSc. Finally, the presence of rheumatoid factor is associated with arthritis, and high MRSS is associated with finger contractures and digital ulcers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…16 On the contrary, limited studies from Asian countries reported variable results ranging from 9% in Thailand, 29% in Turkey, and 71% in China. 15,30,31 The statistically different prevalence of arthritis between the two nations of this study may come from the routine prescription of lowdose steroid for the SSc patients in Iran. This can probably justify the lower prevalence of pericardial effusion among Iranian patients than in French cases (3% vs 10.4%, p-value adj = 0.041).…”
Section: Discussionmentioning
confidence: 90%
“…16 On the contrary, limited studies from Asian countries reported variable results ranging from 9% in Thailand, 29% in Turkey, and 71% in China. 15,30,31 The statistically different prevalence of arthritis between the two nations of this study may come from the routine prescription of lowdose steroid for the SSc patients in Iran. This can probably justify the lower prevalence of pericardial effusion among Iranian patients than in French cases (3% vs 10.4%, p-value adj = 0.041).…”
Section: Discussionmentioning
confidence: 90%
“…Similarly, the EUSTAR registry has shown the significant association of TFR with joint contracture and digital ulcers (17). Moreover, the multivariate analysis reinforced the correlation of hand and finger mRSS with digital ulcer development in the Thai SSc registry (18). The association of the digital ulcers and delta FTP can be justified by the probable association of hand movement and blood circulation in the fingers.…”
Section: N Discussionmentioning
confidence: 76%
“…While the frequency of some ndings such as foot subluxation in past studies were close and ranging from 13.1% (3) to 16% (5) ; there were ndings like hand joint space narrowing with controversial reported frequencies, ranging from 17.9% (6) to 75.3% (7) . Most reports on the prevalence of radiological involvements in SSc were on hand and from Western countries (Europe (3)(4)(5)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) , Canada (18) , United States (19,20) and Africa (21) with only four previous reports from Asia (6,(22)(23)(24) . Few studies evaluated radiologic changes in the feet and they were from Europe (3,5,25) , Africa (21) and only one old from Asia (26) .…”
Section: Introductionmentioning
confidence: 99%